2017
DOI: 10.1016/j.jece.2017.10.031
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sediment properties and experimental variables on the efficiency of electrodialytic removal of metals from sediment

Abstract: Chemometrics was used to determine the influence of sediment properties and experimental settings for the electrodialytic removal (EDR) of Cu, Pb and Zn from six harbour sediments from Greenland and Norway. A Projection onto latent structures (PLS) model revealed that the most important sediment properties for achieving acidification (lag-phase, pH>4), necessary for desorbing and mobilising metals in the polluted sediments, were buffer capacity and grain size distribution. Higher stirring rate reduced the acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…With the help of the Pearson correlation analysis between the heavy metal content in the sediment and the physical-chemical factors under different experimental conditions, we found that pH has a positive effect on the content of most heavy metals in the sediments of still water (Table 3). In general, the heavy metals can achieve high desorption from the sediment at low pH values (Pedersen et al 2017;Adenuga et al 2019;Kobayashi et al 2020). In our experiment, the sedimentary environment is more acidic than the overlying water environment (the pH column in Figure 8 was below the polygonal line).…”
Section: Characteristics Of Heavy Metals In Riverbed Sediments Under Different Circumstances Of the Perturbation Experimentsmentioning
confidence: 64%
“…With the help of the Pearson correlation analysis between the heavy metal content in the sediment and the physical-chemical factors under different experimental conditions, we found that pH has a positive effect on the content of most heavy metals in the sediments of still water (Table 3). In general, the heavy metals can achieve high desorption from the sediment at low pH values (Pedersen et al 2017;Adenuga et al 2019;Kobayashi et al 2020). In our experiment, the sedimentary environment is more acidic than the overlying water environment (the pH column in Figure 8 was below the polygonal line).…”
Section: Characteristics Of Heavy Metals In Riverbed Sediments Under Different Circumstances Of the Perturbation Experimentsmentioning
confidence: 64%
“…It is, however, evident that a much longer treatment would be needed to dissolve all calcium carbonate in the two carbonaceous sediments and obtain a pH drop similar to the one observed for the Raadvad sediment, which is likely to be required to obtain further heavy-metal remediation. Buffer capacity has indeed been mentioned in numerous earlier works as a decisive parameter for the remediation time also when treating other types of materials such as soil fines and harbor sediment [29,30]. Some reduction of the organic matter content was observed for the Raadvad stack-experiment, while not for any of the other experiments, indicating that the dissolution of organic matter occurs only at low pH and is not induced by the current in itself.…”
Section: Sediment Value For Soil Amendment Purposesmentioning
confidence: 64%
“…The feasibility of electrodialytic remediation (EDR) of sludge contaminated by heavy metals when suspended in an aqueous solution was documented earlier for other types of sediments and sludge, e.g., by removal of Cu, Pb, and Zn from harbor sediments [9,10] and extraction of P, Cd, Cu, Cr, Pb, Zn, Ni from wastewater sludge [11]. Only few studies were, however, made on freshwater sediments: Virkutyte and Sillanapää [12] showed that hindering the development of an alkaline front by use of a cation exchange membrane (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…Ribeiro et al 66 Velizarova et al 83 Removal of Cu from a real soil sampled at a wood preservation site in presence of different types of construction refuse in the soil on ED Pedersen et al 69 Ribeiro et al 87 Remediation of MSWI fly ash Ottosen et al 92 (1) Guedes et al 93 (2) Ottosen et al 78 (3) wileyonlinelibrary.com/jctb Pedersen et al 94,95 Options for application: a to treat the solid as stationary or b to treat the solid as a suspension.…”
Section: Overview Of Current Situation Of Lib Recycling Processesmentioning
confidence: 99%